EVALUATION OF THE EXPRESSION OF REACTIVE OXYGEN SPECIES (EROS) AND NITROGEN SPECIES (ERNS) IN CRYOPRESERVED HEMATOPOIETIC STEM CELLS OF ONCOHEMATOLOGICAL PATIENTS - FZ Piazera; S Kuckelhaus; JVP Neto; LHA Ramos; RS Vasconcelos (Hematology, Transfusion and Cell Therapy, 2024)
Introduction: The biology of HSCs is strongly regulated by Oxidative Stress (OS), controlling Reactive Oxygen Species (ROS) levels is important to maintain their ability to self-renew. Both cryopreservation and collection factors, donor characteristics, thawing can release reactive oxygen molecules and trigger cellular stress and loss of HSC integrity. Materials and methods: In the present study, we evaluated the relative expression of EROS and ERNS between a group of 14 patients with hematological malignancies who underwent autologous BMT and 3 healthy controls (donors de HSC voluntaries). Both ROS and ERNs were taken on the LSR FortessaTM cytometer (BD, Biosciences Pharmingen, California, USA) with at least 10×103 events. The results were expressed as a percentage of the average fluorescence intensity (%MFI) by FlowJo Software (Tree Star Inc). Results: The clinical, epidemiological and biological parameters of the individuals studied are presented in Table 1. The results showed great variation in the production of both reactive species, ROS (0.1% MFI ± 0.0% MFI to 63.2% MFI ± 2.6% MFI) and ERNs (0.0% MFI ± 0.0% MFI to 67.5% MFI ± 19.4% MFI); in two samples there was no production of ROS (nº 12 and 13) or ERNs (nº 13 and 14). The use of 20 ng/mL of TNF was not effective in stimulating the production of ROS by the HSC pool (0.0% MFI ± 0.0% MFI), however it did stimulate a small production of ERNs (0.2% MFI ± 0.1% MFI). The use of 50 ng/mL of LPS stimulated the production of ROS (20.1% MFI ± 35.6% MFI) and ERNs (20.0% MFI ± 35.3% MFI). The analysis for the set of samples showed higher production of ERNs (45.4% MFI ± 12.9% MFI) than of ROS (33.1% MFI ± 13.7% MFI) (t-test; p = 0.029). The only finding of association between ROS high expressors was HLA typification, in which individuals 3,9,10 had a predominance of the A*02 allele and were male. The results found in the analysis of the ERNS release pattern, establishing a cut-off value above 35% of MFI for the high expressed ones, there was a slight tendency for individuals with higher percentage rates of MFI to be older than 35-years and with longer cryopreservation periods (above 24-months and less than 55-months). Only two individuals (nº 13 and 14) presented absence of expression of ERNs and respectively presented cryopreservation times greater than 55-months, individual 13- with 55-months and individual 14- with 62-months. Conclusions: The expression of reactive species by HSCs after cryopreservation showed great individual variability. An association was found between ERNS expression and cryopreservation time. Thus, additional studies are needed to elucidate the pattern of association between ERNS and ROS in the viability of HSC.